Aedes albopictus and Aedes japonicus - two invasive mosquito species with different temperature niches in Europe. Issue 1 (December 2016) - Cunze, Sarah; Koch, Lisa; Kochmann, Judith; Klimpel, Sven
Abstract Background Aedes albopictus andAe. japonicus are two of the most widespread invasive mosquito species that have recently become established in western Europe. Both species are associated with the transmission of a number of serious diseases and are projected to continue their spread in Europe. Methods In the present study, we modelled the habitat suitability for both species under current and future climatic conditions by means of an Ensemble forecasting approach. We additionally compared the modelled MAXENT niches ofAe. albopictus andAe. japonicus regarding temperature and precipitation requirements. Results Both species were modelled to find suitable habitat conditions in distinct areas within Europe:Ae. albopictus within the Mediterranean regions in southern Europe, Ae. japonicus within the more temperate regions of central Europe. Only in few regions, suitable habitat conditions were projected to overlap for both species. WhereasAe. albopictus is projected to be generally promoted by climate change in Europe, the area modelled to be climatically suitable forAe. japonicus is projected to decrease under climate change. This projection of range reduction under climate change relies on the assumption thatAe. japonicus is not able to adapt to warmer climatic conditions. The modelled MAXENT temperature niches ofAe. japonicus were found to be narrower with an optimum at lower temperatures compared to the niches ofAe. albopictus. Conclusions Species distribution models identifying areas with high habitat suitability can help improving monitoring programmes for invasive species currently in place. However, as mosquito species are known to be able to adapt to new environmental conditions within the invasion range quickly, niche evolution of invasive mosquito species should be closely followed upon in future studies.